Emotion dysregulation mediates the influence of relationship difficulties on non-suicidal self-injury behavior in young adults. Issue 3 (30th August 2015) - Yurkowski, Kim; Martin, Jodi; Levesque, Christine; Bureau, Jean-François; Lafontaine, Marie-France; Cloutier, Paula
Abstract: This study examined associations between relationship difficulties with parents and peers and non-suicidal self-injury (NSSI). Particular emphasis was placed on examining mediating pathways through emotion dysregulation, as per commonly accepted theory. Participants were 1153 university students (905 females; M age =19.35 years, S.D.=1.49); 79 of these participants had engaged in NSSI during the previous 6 months (63 females, M age =19.35 years, S.D.=1.51). Participants completed questionnaires assessing NSSI, quality of relationships with parents and peers, and emotion dysregulation. Hierarchical logistic regressions suggest that the quality of parent–child relationships has a greater impact on the prediction of NSSI engagement than the quality of peer relationships. Results of a structural equation model showed that feelings of alienation in both parent and peer relationships had indirect effects on NSSI through deficits in emotion regulation (ER). Results suggest the importance of examining emotion dysregulation in association with NSSI, and that both parent and peer relationships are implicated in NSSI engagement through emotion regulation deficits. Important clinical implications regarding the need to acknowledge both emotion dysregulation and interpersonal difficulties when treating NSSI in young adults are discussed. Highlights: Results indicate NSSI treatment strategies should promote emotion regulation skills. NSSI treatment should also consider certain aspects of parent and peer relationships. NSSI research would greatly benefit from prospective, longitudinal investigations. Further research should incorporate population-based samples of self-injurers.